Integrating the objectives of sustainable development into development plans through strategic environmental assessment - Ariffin, Ishak; Abdullah, Muhammad Faris (2002)
Since the introduction of environmental impact assessment (EIA) in Malaysia in the 1970s, environmental assessments (EAs) tools have evolved into a comprehensive and versatile instrument for natural resource planning and management. Other EA tools, such as the cumulative effects assessment (a local variation known as Macro-EIA) and strategic environmental assessment (SEA) have also been introduced in recent years. The EIA looks at project level assessment. Macro EIA deals at cumulative impact assessment. SEA complements the EIA procedures by providing a means to anticipate and prevent impacts at an earlier stage, i.e. at the strategic levels. This paper discusses the application of SEA in integrating sustainable development objectives into development plans in Malaysia. The SEA strengthens the existing development plan system to meet sustainability goals embodied in Agenda 21.